Cone beam computed tomography study of apical root resorption induced by Herbst appliance - Schwartz, Joao Paulo [UNESP]; Raveli, Taisa Boamorte [UNESP]; Mathias Almeida, Kelei Cristina de [UNESP]; Schwartz-Filho, Humberto Osvaldo; Raveli, Dirceu Barnabe [UNESP] (Univ Sao Paulo Fac Odontologia Bauru, 2015)
Objective: This study evaluated the frequency of root resorption during the orthodontic treatment with Herbst appliance by Cone Beam Computed Tomography (CBCT). Material and Methods: The sample comprised 23 patients (11 men, 12 women; mean ages 15.76 +/- 1.75 years) with Class II division 1 malocclusion, treated with Herbst appliance. CBCT was obtained before treatment (T0) and after Herbst treatment (T1). All the dental roots, except third molars, were evaluated, and apical root resorption was determined using the axial guided navigation method. Paired t-tests and Wilcoxon T Test were used to compare the dependent samples in parametric and nonparametric cases, respectively. Chi-Square Test with Yates' correction was used to evaluate the relationship between apical root resorption and gender. esults were considered at a significance level of 5. Results: Apical resorption was detected by CBCT in 57.96% of 980 roots that underwent Herbst appliance treatment. All patients had minimal resorption and there was no statistical significance between the genders. Conclusion: CBCT three-dimensional evaluation showed association between Herbst appliance and minimal apical root resorption, mostly in the anchoring teeth, without clinical significance.
Keywords: Root resorption; Activator appliances; Cone-beam computed tomography